The Impact of the We-Trend on Sustainability and Individualization in Consumer Behaviour - As Shown on the Example of Jarfood GmbH - Anna Schumacher (2018)
This paper investigates the impact of the newly emerged We-trend on the existing trends sustainability and individualization regarding the consumption behaviour of German consumers. It also provides a first analysis of the synergy effect of the analyzed trends. Theoretical approaches and theories provide an overview of the general impact of trends on purchasing behaviour with a special emphasis of the discussed trends. The derived theories were verified by an empirical study in the form of an observation, which firstly compares individual purchasing behaviour with collective purchasing behaviour and further contrasts those observed patterns with two Generations - Generation We and Generation Baby Boomer. On basis of these verifications implications for corporations, food corporations in particular, were extracted and recommendations for actions were formulated. Both theoretical approaches and practical realization resulting from the verification of the empirical observation were explained and put into practice with the example of Jarfood GmbH.